Echocardiographic study of the coronary sinus in the indeterminate form of Chagas disease - Machado, Glauco André (2018)
INTRODUCTION: We investigated the occurrence of coronary sinus abnormalities in the indeterminate form of Chagas disease (CD). METHODS: Differences between the maximum and minimum diameters of the coronary sinus (∆%) on echocardiography were evaluated in individuals with the indeterminate form of CD (n=14) and those without (n=16) CD. The association of the difference with abnormalities detected by echocardiography and myocardial scintigraphy was assessed. RESULTS: The mean Δ% values did not differ significantly between the groups. There was no correlation of the measurements with echocardiographic and myocardial scintigraphy findings. CONCLUSIONS: The coronary sinus evaluation revealed no differences between the groups.